"If you can't measure it, it doesn't exist"? Popular education in the shadows of global reporting on adult learning and education. Issue 1 (2nd January 2019) - Walters, Shirley; von Kotze, Astrid
Abstract: Discourses on adult learning and education (ALE) and in particular the GRALE Report generally have limited coverage of popular education as part of its ecology. Given both the long history of popular education globally as a necessary approach towards affecting transformation and the socio-economic-ecological transformations that are needed, we identify the challenge of incorporating the radical approach of popular education more explicitly into ALE discourses. We proffer suggestions toward this end.